Combination therapy with dendritic cell vaccine and programmed death ligand 1 immune checkpoint inhibitor for hepatocellular carcinoma in an orthotopic mouse model - Chiao-Fang Teng (SAGE Publishing, 2020)
Background: Hepatocellular carcinoma (HCC) is among the most common and lethal human cancers worldwide. Despite remarkable advances in treatment, high mortality in HCC patients remains a big challenge. To develop novel therapeutic strategies for HCC is thus urgently needed to improve patient survival. Dendritic cells (DC)-based vaccines can induce tumor-specific immunity and have emerged as a promising approach for treating HCC patients; however, its effectiveness needs to be improved. Recently, blockade of programmed death ligand 1 (PD-L1) immune checkpoint pathway has been shown to enhance anti-tumor immune responses and exhibited great potential in HCC therapy. Methods: In this study, we generated DC vaccine by pulsing the C57BL/6J mouse bone marrow-derived DC with mouse hepatoma Hep-55.1C cell lysate. We developed a therapeutic strategy combining DC vaccine and PD-L1 inhibitor for HCC and evaluated its efficacy in an orthotopic HCC mouse model in which Hep-55.1C cells were directly injected into left liver lobe of C57BL/6J mouse. Results: Compared with a control group of mice, groups of mice treated with DC vaccine or PD-L1 inhibitor had significantly improved overall survival, reduced tumor volume, and increased tumor cell apoptosis. Remarkably, combination treatment with DC vaccine and PD-L1 inhibitor led to considerably longer overall survival, smaller tumor volume, and higher tumor cell apoptosis of mice than either treatment alone in a dose-dependent manner through inducing a stronger anti-tumor cytotoxic T cell response. Conclusion: Our data suggested that combination therapy with DC vaccine and PD-L1 inhibitor might have great promise as a novel treatment strategy for HCC.